Online edition «The New York Times»: convergence, creolisation and genre variety - Luschinskaya, Olga V. (Journal of the Belarusian State University. Journalism, 2021)
The article considers online edition «The New York Times» as a convergent medium. Its structural and organisational as well as content characteristics are studied. To carry out the analysis a number of formal criteria are taken into account. These criteria allow to identify the design, structure, hierarchy of the site components and other peculiarities. The content of the electronic version as a whole and its media texts in particular are researched with the help of intra and extralinguistic parameters identification. These parameters are reflected by the following discourse categories: audience, selfidentification, time, space, intertextuality, intereventness, intersubjectivity and stylistic range. The degree of presence of the phenomenon of convergence and the phenomenon of creolisation on the American website is studied. The genre variety of media texts and their formats in the electronic version of «The New York Times» are determined. The results are presented in percentage terms.
Keywords: convergence; convergent media; online edition «The New York Times»; discourse categories